The Indexical Voice: Communication of Personal States and Traits in Humans and Other Primates - Locke, John L. (Frontiers in Psychology, 2021)
Many studies of primate vocalization have been undertaken to improve our understanding of the evolution of language. Perhaps, for this reason, investigators have focused on calls that were thought to carry symbolic information about the environment. Here I suggest that even if these calls were in fact symbolic, there were independent reasons to question this approach in the first place. I begin by asking what kind of communication system would satisfy a species’ biological needs. For example, where animals benefit from living in large groups, I ask how members would need to communicate to keep their groups from fragmenting. In this context, I discuss the role of social grooming and "close calls," including lip-smacking and grunting. Parallels exist in human societies, where information is exchanged about all kinds of things, often less about the nominal topic than the communicants themselves. This sort of indexical (or personal) information is vital to group living, which presupposes the ability to tolerate, relate to, and interact constructively with other individuals. Making indexical communication the focus of comparative research encourages consideration of somatic and behavioral cues that facilitate relationships and social benefits, including cooperation and collaboration. There is ample room here for a different and potentially more fruitful approach to communication in humans and other primates, one that focuses on personal appraisals, based on cues originating with individuals, rather than signals excited by environmental events.